Effect of Steam Explosion Pretreatment on Nutritional and Antioxidant Properties of Rapeseed Oil - HUANG Ying, ZHENG Chang, ZHOU Qi, LIU Changsheng, LI Wenlin (Shipin Kexue)
In this study, rapeseed seeds were subjected to steam explosion pretreatment (0.4–1.4 MPa) and then cold-pressed into oil. The microstructures of the untreated and treated seeds were characterized by transmission electron microscopy (TEM), and the quality of rapeseed oil was comprehensively evaluated by measuring fatty acid profiles, functional components, and antioxidant capacity. The results showed that after treatment, the seeds’ cell structure became incomplete, accompanied by oil accumulation and protein denaturation. As the explosion pressure increased, the moisture content gradually declined from 42.17% to 92.24%, and the oil yield initially increased and then decreased, and the contents of oleic acid, linoleic acid, and α-linolenic acid significantly changed. The energy generated during steam explosion pretreatment could effectively destroy active substance complexes, resulting in the release of more free polyphenols, so that the average content of total phenols in the treatment group was increased by 9.56 folds on average when compared with the control group. Especially, the content of 2,6-dimethoxy-4-vinylphenol reached a maximum value of 2 157.95 mg/kg. Phenolic compounds could chelate metal ions, consequently enhancing antioxidant activity of the oil. Specifically, the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity and ferric ion reducing antioxidant power (FRAP) were increased on average by 13.12 and 12.62 folds, respectively. Meanwhile, the contents of tocopherols and phytosterols increased first due to the dissolution of lipid concomitants, and then decreased due to thermal degradation. Multiple antioxidant components could work together to prolong the induction period of the oxidation of the treated oil up to 22.92 h. In summary, steam explosion pretreatment effectively improved the nutritional and antioxidant properties of rapeseed oil.